Studies of Peruvian Ptiliidae (Coleoptera) 5: Chaska nawi, a new genus and species of Acrotrichinae, Acrotrichini - Darby, Michael (Zootaxa, 2016)
Chaska, a new monotypic genus of Acrotrichinae, Acrotrichini with its single species nawi is described and figured. Superficially similar to the more rounded species of Acrotrichis but distinguished by ventral characters in particular the form of the mesoventral collar and the rounded pronotal hind angles. The insect was collected by Dr Caroline Chaboo and her students at the University of Kansas as part of an inventory of leaf beetles in Peru. The name chosen as the winning entry in a national competition to name a beetle species and raise awareness about cryptic biodiversity.